Conserved regions of the Plasmodium falciparum rhoptry-associated protein 3 mediate specific host-pathogen interactions during invasion of red blood cells (2010)
Invasion of red blood cells (RBCs) by the Plasmodium falciparum malaria merozoite is mediated by parasite surface molecules and proteins contained within apical organelles that are capable of recognizing receptors on the membrane of RBCs. The identification and characterization of these P. falciparum invasion-associated proteins is the first step for unveiling potential new drug and vaccine target molecules to eradicate this deadly disease. Among the exclusive set of malarial vaccine candidates, the members of the rhoptry-associated protein (RAP) family have been associated with the parasite's binding to and invasion of RBCs. Remarkably, the third member of this family (named RAP-3) has been recently detected on the surface of non-infected RBCs exposed to free merozoites, therefore suggesting the participation of this protein during RBC infection. In this study, the sequence of RAP-3 was finely mapped using synthetic peptides in order to identify which are the specific binding regions involved in RAP3-RBC interactions. Two high-activity binding peptides (HABPs) established high affinity interactions with RBC surface molecules of about 27-90 kDa, which were differentially affected by different enzymatic treatments. RAP-1 and RAP-2 HABPs inhibited binding of RAP-3 HABPs to different extents, thus suggesting the recognition of similar binding sites on RBC membrane, as well as ability of RAP-3 HABPs to inhibit P. falciparum infection in vitro. Altogether, these functional analyses of RAP-3 HABPs strongly suggest a potential role for this protein in RBC invasion, and highlight its HABPs as potential targets to develop a fully protective minimal subunit-based malarial vaccine. © 2010 Elsevier Inc. All rights reserved.